PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI CANVA BERBASIS MASALAH PADA TEMA EKOSISTEM KELAS V SD - putri fadhillah; nurjannah (PGSD UMN Al-Washliyah, 2023)
This study aims to: (1) develop media using Canva applications in elementary thematic learning, (2) determine the feasibility of developing Canva applications in elementary thematic learning. This research is a type of Research and Development (R&D) research with the ADDIE model which includes five steps, including: analysis, Design, Development, Implementation, Evaluation. The subjects in this study were media expert validators, material experts, education practitioners, namely fourth grade teachers and fourth grade elementary school students. The research instruments used in data collection were questionnaires, observations and documentation. The results of this study indicate that the Canva Application learning media in the Thematic Learning of the Ecosystem Theme for Grade V Elementary School is